Design and Development of a Hybrid Piezoelectric–Electromagnetic Seesaw Energy Harvesting System - Teo, Golbandrio (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study designed and developed a hybrid piezoelectric–electromagnetic seesaw energy harvesting system that converts mechanical energy from footfall pressure and seesaw oscillation into usable electrical energy. The study was anchored on the principles of piezoelectricity and electromagnetic induction, integrating piezoelectric transducers, a DC generator, rectification, energy storage, and voltage boosting in one prototype. A developmental and experimental research design was used. The main research instrument was the hybrid seesaw prototype, which was tested under predetermined load conditions of 40 kg, 50 kg, 60 kg, and 70 kg to represent varying user weights. Data were gathered by measuring voltage and current outputs from the piezoelectric footfall system and DC generator during one-minute trials. Results showed that piezoelectric voltage generally increased as applied load increased, with average outputs ranging from 6.65 V at 40 kg to 15.59 V at 70 kg, while current remained relatively stable. The DC generator also produced usable output from seesaw motion, and the overall prototype achieved an average voltage of 14.4 V and a maximum current of 16.65 mA. The study concluded that the hybrid seesaw system is feasible as a micro-scale energy harvesting device for low-power applications, although its output remains limited and dependent on user weight and frequency of use. The study supports SDG 7, SDG 9, SDG 11, SDG 12, and SDG 4 by promoting clean energy, innovation, sustainable communities, responsible energy use, and applied renewable energy learning. Its sustainability impact lies in technological, environmental, educational, and community-based energy innovation.